Drag Reduction of Complex Mixtures - Watanabe, Keizo (Academic Press, an imprint of Elsevier, 2018)
"Drag Reduction of Complex Mixtures discusses the concept of drag reduction phenomena in complex mixtures in internal and external flows that are shown experimentally by dividing flow patterns into three categories. The book is intended to support further experiments or analysis in drag reduction. As accurately modeling flow behavior with drag reduction is always complex, and since drag reducing additives or solid particles are mixed in fluids, this book covers these complex phenomena in a concise, but comprehensive manner.Comprehensively addresses a range of drag reduction themes involving different kinds of complex mixtures. Provides data to support further experimentation and computer modeling of drag in complex flow. Includes an introduction to the nature and characteristics of different kinds of complex mixtures"--